PLURALITAS PEMAHAMAN AKAN IDENTITAS GEREJA KATOLIK Perkembangan Pembaruan Eklesiologi Gereja Katolik Roma - Purwanto, Fransiskus (P3TK, Sanata Dharma University, 2014)
The presence of the Franciscans and Dominicans in the XIII century had reshaped the ecclesiology on local Church. This new understanding has helped the Church to be more responsive to the need of the people of God and the signs of the times. Luther and the Reformation challenged the Catholic Church to find a new way of being Church. A Church that overemphazied its structure, laws and superior organization (societas perfecta) was deeply questioned. On the other hand, the Holy Spirit of renewal could not be contained by a single reformation. The development in Patristic studies, Scriptures, lay movement, ecumenism as well as renewal in liturgy gave birth to a new ecclesiology that listens to the Holy Spirit seriously, and also the Scriptures as well as participation of the entire people of God as Christs mystical body in building unity. These various movements of renewal will eventually be discerned and attended by the Second Vatican Council.